Paradigms of Library and Information Science in the Networked Society - Krauls, Ineta (Bibliotheca Lituana, 2012)
Essential premises and problems of the Library and Information Science (LIS) paradigms’ shift (uncertainty of scientific boundaries and fragmentation; various historical, sociological and organizational conditions) are analyzed on the case of Vilnius University. Since 1949 Lithuanian university studies and research in the field of LIS had experienced few changes (periods of paradigm shift), that essentially had been preconditioned by general LIS and society’s development tendencies. The case of Vilnius University allows us detect humanitarian, sociological, informational and communicational paradigms. Their formation takes the background in the epistemological relations of LIS to the other sciences and in the necessity to solve practical problems of libraries as well as other information institutions. One of the major challenges that LIS has to face is the requirement to research complicated questions: information services to the society in general as well as individuals; information needs; work of information institutions. Multidimensional problems of LIS field require interdisciplinary view as well as methodological and theoretical transformations. Constant interaction of LIS with other science fosters interdisciplinary research fields and threatens the integrity of LIS on theoretical and methodological levels. Instability of LIS status displays itself not only in theoretical, but also in organizational aspects. Uncertain limits of LIS and tight relations with other sciences enforce dissociation or integration of academic units, while extensive amount of research tasks in LIS field is hardly being performed due to the lack of personnel.